Anti-inflammatory and Neuropharmacological activities of the seed extract of Setaria italica - Tumpa Dasgupta, Saikat Kumar Poddar, Amlan Ganguly, Nazmul Qais (Journal of Applied Pharmaceutical Science, 2016)
Setaria italica (Poaceae) has been used in folk medicine to treat inflammation, pain, arthralgia and many neurological disorders. The objective of the study is screening of ethanolic extract of Setaria italica seeds for possible anti-inflammatory and neuropharmacological activities in rats and mice respectively. Anti-inflammatory activity was evaluated by carrageenan induced paw edema inhibition method while the neuropharmacological potential was evaluated by three separate methods: Hole-cross test, Open-field method and Phenobarbitone induced sleeping time test. The crude ethanolic extract of seeds of Setaria italica at 400 mg/kg body weight showed a strong anti-inflammatory activity with 20.16, 65.44, 65.5 and 71.15% inhibition of paw edema respectively after 1st, 2nd, 3rd and 4th hrs of carrageenan injection which is comparable to that of standard drug diclofenac sodium at 100 mg/kg body weight (% inhibition 92.3% at 4th hour **P
Keywords: Setaria italica, Poaceae, Anti-inflammatory, Open-field, Hole-cross, CNS-depressant.